Musical practice and cognitive aging: two cross-sectional studies point to phonemic fluency as a potential candidate for a use-dependent adaptation - Fauvel, Baptiste; Groussard, Mathilde; Mutlu, Justine; Arenaza-Urquijo, Eider M.; Eustache, Francis; Desgranges, Béatrice; Platel, Hervé (Frontiers in Aging Neuroscience, 2014)
Because of permanent use-dependent cerebral plasticity, all lifelong individuals’ experiences are believed to influence the cognitive aging quality. In old individuals, both former and current musical practices have been associated with better verbal skills, visual memory, processing speed, and planning function. This work sought for an interaction between musical practice and cognitive aging by comparing musician and nonmusician individuals for two periods of life (late adulthood and old age). Long-term memory, auditory verbal short-term memory, processing speed, nonverbal reasoning, and verbal fluencies were assessed. In study 1, measures of processing speed and auditory verbal short-term memory showed significant better performances for musicians compared with controls, but both groups displayed the same age-related difference. For verbal fluencies, musician individuals scored higher and displayed different age effects compared with controls. In study 2, we revealed that the life period at training onset (childhood versus adulthood) was associated with phonemic, but not semantic fluency performances (musicians who had started practice in adulthood did not perform better on phonemic fluency compared with nonmusicians). For these two measures, current frequency of training did not account for musicians’ scores. These patterns of results are discussed by confronting the hypothesis of a transformative effect of musical practice with non-causal explanation.